(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Endometrial growth plays a critical role in female reproductive health, particularly in processes such as menstruation, implantation, and pregnancy. This thesis explores the mechanisms of endometrial growth induction, emphasizing the interplay between hormonal, molecular, and cellular factors that regulate the endometrial cycle. It further examines the therapeutic applications of inducing endometrial growth in conditions like endometrial atrophy, infertility, and uterine disorders, alongside the potential challenges and risks associated with these interventions. Emerging therapeutic strategies, including hormonal therapies, growth factors, and regenerative medicine, are evaluated for their efficacy and safety. Through an exploration of clinical studies and experimental models, this thesis aims to provide a comprehensive understanding of how endometrial growth induction can enhance reproductive outcomes, improve gynecological health, and address fertility issues.